HUBUNGAN PENGETAHUAN DAN DUKUNGAN KELUARGA DENGAN KEPATUHAN DIET PASIEN DIABETES MELITUS TIPE 2 DI PUSKESMAS KAYON KOTA PALANGKA RAYA - Dinda Anindita Salsabilla; Yana Afrina (Medic Nutricia : Jurnal Ilmu Kesehatan, 2024)
Diabetes Mellitus (DM) is a chronic disease in which the body does not produce enough insulin or cannot use insulin effectively. Diabetes is the cause of the largest increase in male deaths among the 10 leading causes of death, with an 80% increase since 2000. This study aims to determine the relationship between knowledge and family support with dietary compliance in patients with type 2 diabetes mellitus at Kayon Health Center, Palangka Raya City. This study is a quantitative study with a cross sectional design. This study was conducted on 52 patients with type 2 diabetes mellitus at Kayon Health Center who met the inclusion and exclusion criteria using purposive sampling technique. Data analysis using Chi Square test. The results showed knowledge p-value = 0.670 > 0.05, which means there is no significant relationship between the level of knowledge and dietary compliance. Not always people who have good knowledge will adhere to the diet because of the inability of respondents to control eating behavior and food selection, which is not entirely based on the concept of knowledge they have. The study showed a knowledge p-value = 0.034 <0.05, which means there is a significant relationship between family support and dietary compliance. Social support from the family is one of the factors that is closely related to the level of patient compliance in carrying out the diet program